A pilot PTC system installed in an industrial factory of Cyprus: Feasibility for the wider use in the Cyprus industry - Ktistis, Panayiotis K.; Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2018)
A total of 94 % of the energy demand in Cyprus is covered by consuming fossil fuels. Sectors such as transportation and industry are the biggest consumers, corresponding to a consumption of 57 % and 20 % respectively. Apart from the environmental impact from the use of fossil fuels, fuel cost has a direct impact on the country's economy as well. Based on these facts and having as a goal to reach the EU 2020 energy efficiency target, an effective way to reduce the use of fossil fuels and energy consumption, is the use of renewable energy systems. Moreover, it was revealed that the biggest energy consumer from the industrial sector is the food and beverage industry. Solar energy systems that could support the thermal energy needs of these industries are small-scaled middle temperature parabolic trough collectors (PTC) with thermal storage and auxiliary systems. The purpose of this study is to present the first pilot PTC system installed to serve 40 kWth of the thermal needs of a soft drink factory named 'KEAN', located in Limassol, Cyprus. A dynamic simulation modelling is also developed to predict the performance of the system and study its potential to be further utilized in a higher thermal load. For the dynamic modelling of the system, TRNSYS software is used, with weather data from typical meteorological year (TMY) files for Cyprus. It was concluded that KEAN solar system could produce 125 kWth heat from which the 40 kWth are utilized by the industry whereas the rest are stored and used when needed. For a bigger application, for a dairy factory, a year period, and a thermal load of 190 kWth the system with 42 collectors could cover 68% of the load and the auxiliary covers the rest. To examine the potential of this system a life cycle cost analysis (LCCA) has been done. It was concluded that the total investment would have a payback period of 5 y.
Keywords: Solar energy systems; Food and beverage industry; Solar system; Use of renewable energies